Survival analysis of carboplatin added to an anthracycline/taxane-based neoadjuvant chemotherapy and HRD score as predictor of response—final results from GeparSixto. (18th October 2018) - Loibl, S; Weber, K E; Timms, K M; Elkin, E P; Hahnen, E; Fasching, P A; Lederer, B; Denkert, C; Schneeweiss, A; Braun, S; Salat, C T; Rezai, M; et al.
Abstract: Background: In the neoadjuvant GeparSixto study, adding carboplatin to taxane- and anthracycline-based chemotherapy improved pathological complete response (pCR) rates in patients with triple-negative breast cancer (TNBC). Here, we present survival data and the potential prognostic and predictive role of homologous recombination deficiency (HRD). Patients and methods: Patients were randomized to paclitaxel plus nonpegylated liposomal doxorubicin (Myocet ® ) (PM) or PM plus carboplatin (PMCb). The secondary study end points disease-free survival (DFS) and overall survival (OS) were analyzed. Median follow-up was 47.3 months. HRD was among the exploratory analyses in GeparSixto and was successfully measured in formalin-fixed, paraffin-embedded tumor samples of 193/315 (61.3%) participants with TNBC. Homologous recombination (HR) deficiency was defined as HRD score ≥42 and/or presence of tumor BRCA mutations (tm BRCA ). Results: A significantly better DFS (hazard ratio 0.56, 95% CI 0.34–0.93; P  =   0.022) was observed in patients with TNBC when treated with PMCb. The improvement of OS with PMCb was not statistically significant. Additional carboplatin did not improve DFS or OS in patients with HER2-positive tumors. HR deficiency was detected in 136 (70.5%) of 193 triple-negative tumors, of which 82 (60.3%) showed high HRD score without tm BRCA . HR deficiency independently predicted pCR (ypT0 ypN0) [odds ratio (OR) 2.60, 95% CI 1.26–5.37, P  =   0.008]. Adding carboplatin to PM significantly increased the pCR rate from 33.9% to 63.5% in HR deficient tumors ( P  =   0.001), but only marginally in HR nondeficient tumors (from 20.0% to 29.6%, P  =   0.540; test for interaction P  =   0.327). pCR rates with carboplatin were also higher (63.2%) than without carboplatin (31.7%; OR 3.69, 1.46–9.37, P  =   0.005) in patients with high HRD score but no tm BRCA . DFS rates were improved with addition of carboplatin, both in HR nondeficient (hazard ratio 0.44, 0.17–1.17, P  =   0.086) and HR deficient tumors (hazard ratio 0.49, 0.23–1.04, P  =   0.059). Conclusions: The addition of carboplatin to neoadjuvant PM improved DFS significantly in TNBC. Long-term survival analyses support the neoadjuvant use of carboplatin in TNBC. HR deficiency in TNBC and HRD score in non-tm BRCA TNBC are predictors of response. HRD does not predict for carboplatin benefit.